2020
DOI: 10.1097/j.pain.0000000000001802
|View full text |Cite
|
Sign up to set email alerts
|

An unbiased and efficient assessment of excitability of sensory neurons for analgesic drug discovery

Abstract: Alleviating chronic pain is challenging, due to lack of drugs that effectively inhibit nociceptors without off-target effects on motor or central neurons. Dorsal root ganglia (DRG) contain nociceptive and non-nociceptive neurons. Drug screening on cultured DRG neurons, rather than cell lines, allows for the identification of drugs most potent on nociceptors with no effects on non-nociceptors (as a proxy for unwanted side effects on central nervous system and motor neurons). However, screening using DRG neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Equally important, for the evaluation of any drug combination, is the potential effects on non-nociceptors as well as nociceptors. We recently described a relevant assay [88] and provided proof-of-concept data that showed a combination of Na v 1.7 and Na v 1.8 blockers produced a reduction in the excitability of DRG neurons close to that measured in Na v 1.7 KO [89]. Changing the constituents and doses in VGSC blocker combinations may enable clinicians to manage chronic pain safely over the long term.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Equally important, for the evaluation of any drug combination, is the potential effects on non-nociceptors as well as nociceptors. We recently described a relevant assay [88] and provided proof-of-concept data that showed a combination of Na v 1.7 and Na v 1.8 blockers produced a reduction in the excitability of DRG neurons close to that measured in Na v 1.7 KO [89]. Changing the constituents and doses in VGSC blocker combinations may enable clinicians to manage chronic pain safely over the long term.…”
Section: Discussionmentioning
confidence: 95%
“…Deletion of Na v 1.7 causes an increase in action potential threshold in small-diameter DRG neurons [107]. Deletion of Na v 1.7 causes a major decrease in DRG neuron responsiveness to the VGSC opener veratridine [89]. Mechanically evoked spiking of C-fibres in the skin-nerve preparation was reduced in Na v 1.7 KO mice [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As VTD specifically functions on the Na V channel, these data imply that Narirutin affects Na V rather than Ca V channels. Given that nociceptors and non-nociceptors respond to VTD with distinct response profiles [ 26 ], a VTD-based neuron classification assay helps us to better investigate the potential analgesic mechanism of Narirutin. Generally, VTD elicits four distinct response profiles in sensory neurons: oscillatory (OS), slow decay (SD), rapid decay (RD), and intermediate decay (ID) ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…In animals after MI, however, the same application of nociceptive chemicals affected the activity of a greater proportion (48%) of all cardiac neurons, and the predominant responses observed were inhibitory. It has also been previously shown that acute application of nociceptive chemicals, such as capsaicin, bradykinin ( 36 , 37 ), and veratridine ( 38 ), causes neuronal depolarization and predominantly increases in activity and firing rates of the majority of nociceptive neurons in the peripheral autonomic ganglia when evaluated either in vivo or using whole-cell voltage-clamp recordings ( 39 , 40 ). In vivo nodose recordings from guinea pigs with healthy hearts, which were consistent with the healthy porcine animal data in this study, showed that epicardial application of bradykinin activated the majority (74%) of identified cardiac nociceptive neurons, with a decrease in firing rate observed in only 26% of recorded neurons ( 22 ).…”
Section: Discussionmentioning
confidence: 99%